ANALISIS PERMINTAAN MASYARAKAT TERHADAP PELAYANAN RAWAT JALAN RUMAH SAKIT UMUM DAERAH DR. R. SOETIJONO BLORA - Meitrika Damayanti; Sutopo Patria Jati; Septo Pawelas Arso (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Demand of health service utilization is influenced by economic and non-economic variables. Demand’s analysis is made by the hospital to identify some factors which become strengths and weaknesses, opportunities and threats for the hospital as a basis for preparing the marketing strategy. However, in the era of National Health Insurance (JKN), the number of patient visits the clinic dr. R. Soetijono Blora actually declined in the period of four months from March to June 2016.The purpose of the study is to describe the public demand and identify the factors that influence public demand for outpatient services in RSUD dr. R. Soetijono Blora. This study uses quantitative methods and types of cross-sectional study with 100 respondents who are the patient of polyclinic RSUD dr. R. Soetijono Blora. The results showed that public demand for outpatient services in RSUD dr. R. Soetijono Blora high is (58%). There are significant correlations between age, health insurance ownership, the type of disease, and health beliefs (p <0.05). Factors that affect the public demand for outpatient services in RSUD dr. R. Soetijono Blora are age, health insurance ownership, the type of disease and health beliefs (p <0.05). These factors influence the demand positively with Odd Ratio (OR) values for health belief is 2,667; age is 2,376; health insurance ownership is 3,075 and the type of disease is 2,588. Management can improve intensive marketing especially for the out-of-pocket patient and increase the patients’ trust by optimizing the quality of hospital services because these factors influence the patients to revisit the hospital.